Programming Approach in Teaching Operations Research Techniques for Computer Science Students - Maarop, Nurazean; Masrom, Maslin (2005)
Computer Science (CS) is an applied and interdisciplinary field, and lies at the intersection of mathematics and engineering. Meanwhile, Operations Research (OR) is the art of mathematical modeling and analysis to design, evaluate, or improve the operations of a real-world systems. It is essentially identical to the systems analysis. OR techniques include among others, linear programming, non-linear programming, integer programming, data analysis including statistics, simulation, and goal programming. From the computer science perspective, OR is very essential in defining technical management information system. Most OR techniques are the core elements to model the programming solution. In the typical phases of software development, understanding OR techniques will help students to determine better requirement and specification of any problem that involves OR solution. Furthermore, in order to perform the analysis of the mathematical model, computer science students need to be introduced with the tools of mathematics, algorithm development, and computer programming approach for solving the problems. Therefore, in this paper, we first present the concepts and methods of OR. Programming approach used in teaching OR techniques are identified and discussed at the end of the paper.